Strategi Komunikasi Pemasaran Thrifting Doubleus.Mks Pada Media Sosial Instagram - Fitriani; Syukri; Arni (Jurnal Komunikasi dan Organisasi (J-KO), 2026)
This research is motivated by the importance of marketing communication strategies in increasing consumer attraction and purchase decisions in thrifting businesses in the digital era, particularly through Instagram social media. This study aims to analyze the implementation of the marketing communication strategy of Doubleus.mks in attracting attention, building interest, creating desire, and encouraging consumer purchasing actions. The research employed a qualitative method with a descriptive-analytical approach, using primary and secondary data collected from four informants. The results show that Doubleus.mks implements its marketing communication strategy by utilizing various Instagram features such as Instagram Story, feed posts, Reels, Live Instagram, story highlights, Direct Message (DM), and geotagging to facilitate audience access to store location information and enhance interaction with customers. These strategies are proven effective in delivering consistent marketing messages, building two-way communication between seller and consumers, and increasing purchase intention and buying decisions. In conclusion, the optimal use of Instagram features can serve as an effective marketing communication strategy for thrifting businesses in expanding market reach and strengthening relationships with consumers.